Design of a learning situation based on acrosport and focused on implementing the Cooperative Learning pedagogical model - Ibáñez Velilla, Clara; Zurita Ortega, Félix; Castro García, Ángel; Puertas Molero, Pilar (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study presented an educational proposal focused on the gymnastic discipline of acrosport that applies the Cooperative Learning pedagogical methodology. It was intended for sixth-grade primary school students and aimed to develop and consolidate students' motor skills such as strength, flexibility, balance and coordination, artistic and expressive skills, and socio-emotional competencies derived from collaborative work, such as effective communication, shared effort and group cohesion. Therefore, it was deemed appropriate to focus attention on active and motivating methodological aspects like Cooperative Learning, using responsibility roles to foster student engagement, promoting a climate of trust, and improving self-regulation within the class group.